Monovision versus multifocal intraocular lens implantation in cataract patients: a systematic review and meta-analysis: Oral Presentation - Observational Study - General practitioner - Fadhli Waznan; Yosilia Nursakina; Aydan Jalil Rancakbudi; Syska Widyawati (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Modern cataract surgery technique entails replacing the crystalline lens with an artificial intraocular lens (IOL). While the standard monofocal IOL implantation with monovision technique has been cost- effective and provided patients with good visual acuity, multifocal IOLs present the prospect of spectacle-free vision despite various adverse outcomes. It remained contentious whether multifocal IOLs were superior to monovision. Our review provide an up-to-date assessment of monovision vs. multifocal IOL implantation's visual acuity and spectacle independence following cataract surgery. Methods : A systematic search was performed in April 2023 on six databases (Medline, SCOPUS, Proquest, EBSCO, Embase, and PubMed). Studies were extracted for the following outcome of interest: monovision, multifocal intraocular lens, spectacle independence, and visual acuity. All studies published up to April 2023 were reviewed. Cochrane risk of bias tool (RoB 2) was used to screen studies for risk of bias where appropriate. A meta-analysis was done to quantify any reported quantitative data. Results : Ten studies were identified. Pooling analysis for uncorrected binocular distance visual acuity and binocular uncorrected near visual acuity showed no difference between monovision vs. multifocal IOL (SMD 0,31; 95% CI -0,21 to 0,82 and SMD 0,41; 95% CI -0,58 to 1,40, respectively). Spectacle independence showed monovision was inferior to multifocal IOL (OR 0,22; 95% CI 0,08 to 0,61; heterogeneity I2=75%). Conclusion : Current evidence showed that multifocal IOL had comparable visual acuity to monovision with slightly higher likelihood of being spectacle-free. Despite that, monovision can be an efficacious and affordable option to be implemented in countries with high cataract burden.